Transfiguracja – Piękna złośnica Jacques’a Rivette’a w świetle mimo-sekularnej myśli o filmie i mediach światłowodowych - Bohdziewicz , Janusz (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2021)
The essay is an interpretation of the film by Jacques Rivette La Belle Noiseuse (1991) within the context of post-secular studies. The sketch is inspired primarily by the writings of Martin Heidegger and Jean-Luc Nancy, and it also corresponds with the Bible and biblical studies. The author describes the creative process shown in the film as an act of salvation which occurs between the painter and his model. The hiding of the resulting image is understood here in relation to the passion, cross and burial of Jesus which brings the hope for a liberated life and “the new creation”. The film is made in a very consistent way, which opens up the perspective of crossing the world of images, paintings and classical films (the world of stage), towards the art of mutual respect (the world of interface). Rivette’s work contains a multitude of relevant observations and indications regarding psychology, religion and culture, but it also reveals the possibility of a new way of thinking about film and the media, close to Nancy’s post-metaphysical thought.